Production of monoclonal antibody against male specific antigen on cell membrane of bovine spermatozoa - Patthanawong W. (2014)
The objective of this study was to produce monoclonal antibody (MAb) against Y-bearing spermatozoa. The antibody will be used in cytotoxic immunological reaction on the Y-bearing sperm, which resulted in gender biased semen. Three BALB/c mice were immunized against dairy bull spermatozoa and Freund's complete adjuvant, 106 cells per 100 μl, at two week interval. The spleenocytes, from the mouse that had produced antibodies to the Y-bearing spermatozoa, were used for fusion with the myeloma cells line, X63-Ag8.653, with the aid of polyethylene glycol. It was found, within 14-21 days after fusion, that 148 clones appeared. Three of those clones were capable of binding specifically with white blood cells (WBC) from dairy bulls (n=5) and showed negative response with the WBC from dairy heifers (n=5). The three antibodies were classified to be IgG. One of them, clone number 1F9-3B10, was chosen due to its high antibody activity. The clone was tested by using Immunofluorescent technique with WBC of 20 dairy bulls and 30 dairy heifers, the results showed that 89.5 % of those bull WBC were recognized by the MAb from the clone number 1F9-3B10 (p<0.005). In conclusion, the MAb tends to bind specifically with Y-bearing bull spermatozoa.